Beliefs about NHS stop smoking services and nicotine replacement therapy in pregnancy: exploring the potential role of the theory of planned behaviour in promoting uptake of smoking cessation services - Taylor, John Adam (2010)
A number of women continue to smoke in pregnancy despite the associated risks to their health and that of their unborn child. Little is known about their attitudes towards the smoking cessation support which is available to them and this thesis used a Theory of Planned Behaviour (TPB) approach to investigate this further.